APPLICATION OF ERGONOMICS TO IMPROVE HEALTH AND WORK PRODUCTIVITY IN CLASS A MEDAN SEARCH AND RESCUE OFFICE - Ayu, Delfriana; Chairunnisa, Chairunnisa; Azizi, Hilda Aprilia; Malau, Nurlyani; Hasibuan, Puan Mahrani (HEARTY, 2024)
Ergonomics is a science that studies human behavior about the work carried out, ergonomics is also an applied science which is an interaction that explains the interaction between humans and their workplace. Ergonomics includes examining the physical capabilities of workers, the workplace environment, and the tasks being completed and applying this information to the design of tool models, equipment, and work methods required for overall task safety. A safe, healthy, and comfortable work environment can increase worker productivity. Therefore, K3 plays an important role in increasing productivity, safety, and comfort of workers, precisely at the Medan Class A Search and Rescue Office, it is necessary to apply ergonomics in all areas of work, both indoor workers and workers in the field.